Effect of the number of sprint repetitions on the variation of blood lactate concentration in repeated sprint sessions - Gharbi, Z.; Dardouri, W.; Haj-Sassi, R.; Castagna, C.; Chamari, K.; Souissi, N. (Biology of Sport, 2014)
The aim of the present study was to examine the effect of number of sprint repetitions on the variation of blood lactate concentration (blood [La]) during different repeated-sprint sessions in order to find the appropriate number of sprint repetitions that properly simulates the physiological demands of team sport competitions. Twenty male team-sport players (age, 22.2 ± 2.9 years) performed several repeated-sprint sessions (RSS) consisting of 1, 2, 3, 4, 5, 9, or 10 repetitions of 30 m shuttle sprints (2 × 15 m) with 30 s recovery in between. The blood [La] was obtained after 3 min of recovery at the end of each RSS. The present study showed that for RSS of 3 sprints (RSS3) there was a high increase (p<0.001) in blood [La], which reached approximately fivefold resting values (9.4±1.7 mmol/l) and then remained unchanged for the RSS of 4 and 5 sprints (9.6±1.4 and 10.5±1.9 mmol/l, p=0.96 and 0.26, respectively). After RSS9 and RSS10 blood [La] further significantly increased to 12.6 and 12.7 mmol/l, p<0.001, respectively. No significant difference was found between RSS3, RSS4 and RSS5 for the percentage of sprint speed decrement (Sdec) (1.5±1.2; 2.0±1.1 and 2.6±1.4%, respectively). There was also no significant difference between RSS9 and RSS10 for Sdec (3.9±1.3% and 4.5±1.4%, respectively). In conclusion, the repeated-sprint protocol composed of 5 shuttle sprint repetitions is more representative of the blood lactate demands of the team sports game intensity.